p38α Isoform Mxi2 Binds to Extracellular Signal-Regulated Kinase 1 and 2 Mitogen-Activated Protein Kinase and Regulates Its Nuclear Activity by Sustaining Its Phosphorylation Levels - Sanz-Moreno, Victoria (American Society for Microbiology, 2003)
Mxi2 is a p38α splice isoform that is distinctively activated by mitogenic stimuli. Here we show that Mxi2 immunoprecipitates carry a kinase activity that is persistently activated by epidermal growth factor in a fashion regulated by Ras, Raf, and MEK. We demonstrate that this kinase activity can be attributed not to Mxi2 but rather to extracellular signal-regulated kinases 1 and 2 (ERK1/2), which coimmunoprecipitated with Mxi2 both by ectopic expression and in a physiological environment like the kidney. Furthermore, we provide evidence that Mxi2-ERK interaction has profound effects on ERK function, demonstrating that Mxi2 prolongs the duration of the ERK signal by sustaining its phosphorylation levels. Interestingly, we show that the effects of Mxi2 on ERK are restricted to nuclear events. Mxi2 potently up-regulates ERK-mediated activation of the transcription factors Elk1 and HIF1α but has no effect on the activity of ERK cytoplasmic substrates RSK2 and cPLA(2), induced by epidermal growth factor or by MEK. Overall, our findings point to Mxi2 as a unique member of the p38 family that may have an unprecedented role in the regulation of the functions of ERK mitogen-activated protein kinases.